2015
DOI: 10.1253/circj.cj-15-0425
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Ejection Fraction (EF) of 55% as Cutoff for Late Transition From Heart Failure (HF) With Preserved EF to HF With Mildly Reduced EF

Abstract: Background: Heart failure (HF) with preserved (HFpEF) left ventricular ejection fraction (LVEF) is a syndrome with complex pathophysiology. Little is known about changes in LVEF that occur over time in HFpEF patients. A fundamental clinical question about HFpEF is whether HFpEF is an early manifestation of HF with reduced LVEF (HFrEF). If so, which patients with HFpEF are likely to show a decline in LVEF to less than 50%? The aim of the present study was to examine longitudinal changes in LVEF in patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…This is consistent with the results in our study. In addition, Ueda et al 19. concluded that LVEF ≤ 55% in patients with HFpEF (LVEF > 50%) was significantly associated with a decrease in LVEF to below 50% during a mean follow‐up period of 31.5 ± 17.0 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the results in our study. In addition, Ueda et al 19. concluded that LVEF ≤ 55% in patients with HFpEF (LVEF > 50%) was significantly associated with a decrease in LVEF to below 50% during a mean follow‐up period of 31.5 ± 17.0 months.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we found that the characteristics of patients in the HFrhEF and HFrEF groups were less similar than the characteristics of the HFrlEF and HFrEF groups. Ueda et al 19 demonstrated that patients with HFpEF and LVEF >55% were significantly less likely to have ischaemic heart disease as an aetiology of HF compared with those with HF and 50% < LVEF ≤ 55%. This is consistent with the results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We also excluded 33 patients with LV ejection fraction (EF) ≤55% to simply clarify the effect of TAVI on DF. 12 The remaining 98 patients eligible for analysis formed the study group.…”
Section: Participantsmentioning
confidence: 99%
“…However, using newer diagnostic techniques of myocardial deformation, several studies have shown subtle changes in systolic function including reduced longitudinal strain, impaired systolic twist, torsional dyssynchrony, and reduced myocardial systolic reserve [11]. Also, there is recent evidence that there is slow but progressive decline in ejection fraction in patients with DHF; therefore, these patients will eventually be diagnosed with heart failure with reduced ejection fraction [12,13]. Dunlay et al showed that in patients with DHF, on an average, ejection fraction decreased by 5.8% over 5 years with greater declines in older individuals and in those with coronary artery disease.…”
Section: Systolic Dysfunctionmentioning
confidence: 99%